1995
DOI: 10.1038/nm0995-950
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the obese (ob) gene in adipose tissue of human obese subjects

Abstract: Obesity is accompanied by complications such as hypertension, non-insulin-dependent diabetes mellitus and atherosclerosis, which in turn cause ischaemic heart disease, stroke and premature death. The underlying mechanisms behind imbalance in energy intake and energy expenditure that lead to obesity are still controversial. In most populations, obesity is more common among women than men and is a multifactorial phenotype, which may result from a complex network of genetic and nongenetic factors. The relative im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

36
343
3
20

Year Published

1997
1997
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 662 publications
(402 citation statements)
references
References 21 publications
36
343
3
20
Order By: Relevance
“…The circulating levels of leptin have been shown to be influenced by amount of body fat, with higher levels in obese than in lean individuals [29]. However, conflicting findings are reported for leptin concentration differences with similar fat mass [30,31]. Another study found high plasma leptin levels in obese humans [32], suggesting release of leptin from the adipose tissue in relation to adiposity.…”
Section: Resultsmentioning
confidence: 99%
“…The circulating levels of leptin have been shown to be influenced by amount of body fat, with higher levels in obese than in lean individuals [29]. However, conflicting findings are reported for leptin concentration differences with similar fat mass [30,31]. Another study found high plasma leptin levels in obese humans [32], suggesting release of leptin from the adipose tissue in relation to adiposity.…”
Section: Resultsmentioning
confidence: 99%
“…Leptin causes weight loss in mice by reducing food intake and increasing energy expenditure (2)(3)(4)(5). Furthermore, ob gene expression is increased in human obesity (6)(7)(8)(9) and in various animal models of obesity (10). The accumulated evidence suggests that leptin is important in controlling body weight.…”
mentioning
confidence: 99%
“…Recent studies have shown that although the complete absence of leptin leads to obesity (Ahima and Flier 2000;Zhang et al 1994), leptin at excessive levels does not prompt a lean phenotype (Ahima and Flier 2000;Myers et al 2012). Leptin expression occurs at high levels in animal models of obesity (Frederich et al 1995;Sinha et al 1996) and in human obesity (Lonnqvist et al 1995). This phenomenon is called leptin resistance and is described as a reduced sensitivity with respect to the anorectic response to exogenously administered leptin (Carter et al 2013).…”
Section: Leptinmentioning
confidence: 99%